1981
DOI: 10.1139/v81-056
|View full text |Cite
|
Sign up to set email alerts
|

Betylates. 2. The formation and high reactivity of alkyl [0]betylates

Abstract: . Can. J. Chem. 59,362 (1981). Unhindered primary alkyl N,N-dimethylsulfamates (1) react with methyl fluorosulfate to give the corresponding alkyl fluorosulfates (3) and the betaine, M~,&so,-(4), evidently by way of the intermediate alkyl [Olbetylate fluorosulfate (2); with certain other alkyl esters (1) products of substitution, elimination, and rearrangement are formed. The reaction not only provides a potentially useful route to simple alkyl fluorosulfates, but serves to demonstrate the powerful nucleofugal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Under their optimized reaction conditions, King and Lee reported the synthesis of alkyl fluorosulfates 34 in good yields from the reaction of alkyl N , N ‐diethyl sulfamates ( 90 ) with methyl fluorosulfates (Scheme ) …”
Section: Synthesis Of Fluorosulfatesmentioning
confidence: 99%
“…Under their optimized reaction conditions, King and Lee reported the synthesis of alkyl fluorosulfates 34 in good yields from the reaction of alkyl N , N ‐diethyl sulfamates ( 90 ) with methyl fluorosulfates (Scheme ) …”
Section: Synthesis Of Fluorosulfatesmentioning
confidence: 99%
“…'Phenyl b e t~l a t e '~) (3) has recently been synthesized [30]; nucleophiles reacted with it either by attack at the S-or at the methyl-C-atoms [30]. Alkyl betylates, on the other hand, could not be isolated, but the reaction products indicated that they decompose yielding carbenium ions [31]. A comparison of the extremely short lifetime of alkyl betylates with that of alkyl trifluoromethanesulfonates (triflates) has led to the conclusion that the betylate is a better leaving group than triflate by a factor of more than lo5 [31], and thus with the exception of the diazonio group probably the best leaving group known.…”
mentioning
confidence: 99%